PFLOTRAN-E4D: A parallel open source PFLOTRAN module for simulating time-lapse electrical resistivity data. (February 2017) - Johnson, Timothy C.; Hammond, Glenn E.; Chen, Xingyuan
Abstract: Time-lapse electrical resistivity tomography (ERT) is finding increased application for remotely monitoring processes occurring in the near subsurface in three-dimensions (i.e. 4D monitoring). However, there are few codes capable of simulating the evolution of subsurface resistivity and corresponding tomographic measurements arising from a particular process, particularly in parallel and with an open source license. Herein we describe and demonstrate an electrical resistivity tomography module for the PFLOTRAN subsurface flow and reactive transport simulation code, named PFLOTRAN-E4D. The PFLOTRAN-E4D module operates in parallel using a dedicated set of compute cores in a master-slave configuration. At each time step, the master processes receives subsurface states from PFLOTRAN, converts those states to bulk electrical conductivity, and instructs the slave processes to simulate a tomographic data set. The resulting multi-physics simulation capability enables accurate feasibility studies for ERT imaging, the identification of the ERT signatures that are unique to a given process, and facilitates the joint inversion of ERT data with hydrogeological data for subsurface characterization. PFLOTRAN-E4D is demonstrated herein using a field study of stage-driven groundwater/river water interaction ERT monitoring along the Columbia River, Washington, USA. Results demonstrate the complex nature of subsurface electrical conductivity changes, in both the saturated and unsaturated zones, arising from river stage fluctuations and associated river water intrusion into the aquifer. The results also demonstrate the sensitivity of surface based ERT measurements to those changes over time. PFLOTRAN-E4D is available with the PFLOTRAN development version with an open-source license athttps://bitbucket.org/pflotran/pflotran-dev . Highlights: Subsurface simulator PFLOTRAN is internally coupled with geophysical simulator E4D. E4D runs as a module to PFLOTRAN, using a dedicated set of parallel compute nodes. The coupled code enables the simulation of changes in bulk electrical conductivity. The coupled code enables the simulation of time-lapse electrical resistivity surveys. A simulation of geophysical monitoring of groundwater/river water interaction is demonstrated.